PELATIHANMANAJEMEN KEUANGAN PADA PELAKU USAHATOKO KELONTONGDUSUNPULUHAN, DESA BANYUSIDI, PAKIS, MAGELANG,JAWA TENGAH - Muhammad Hasyim (UII, 2014)
Atraditional grocery store is just one type of micro small businesses in the communitydespite the longer numbers became less and less because it competes with modernminimarket. To be able tocompete with supermarket / modern store, it needed thediscipline, good management and strategy. Financial management in running a smallbusiness is one important aspect that determinesthe success of the business. With goodmanagement, it will obtain a clear profit in number, and there will be the right decision.Training programs to businesses in the hamlet Dozens grocery store can provide insightand provisions on financial management of businesses will.